(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Recently the use of tilted implants has been considered as a preferable option in case of atrophic edentulous arches. The tilted longer implants can be of use to ward off the important anatomical structures while also permitting cantilever reduction. Since the load transfer mechanism of an implant can be altered significantly by the number of implants and its location in the edentulous ridge, the present study evaluates and compares the stress patterns in the edentulous mandibular bone around two implant retained, four implant retained over denture and all on four concepts under different loading conditions using finite element analysis. Purpose: The biomechanical behaviour of the ‘All-On-Four’ system was compared with that of the two implant-supported and four-implant supported mandibular overdenture using the three dimensional finite element method (FEM). Thereby evaluating the von Misses stresses induced on the implants under different loading simulations. Materials & Method: Three dimensional models representing mandible restored with ‘All-On-Four’, two implant-supported and four-implant-supported prosthesis were developed in the three dimensional design software and then transferred into FEM software. The models were then subjected to four different loading simulations (full mouth biting, canine disclusion, load on cantilever, load in the absence of cantilever). The maximum von Mises stresses were localized and quantified for comparison.1 Results: Among the three models, under all loading simulations, the maximum stress concentrations werealong the neck of the implant. The stress levels for full mouth loading simulation was highest for twoimplant supported overdenture design and the least for All-On-Four overdenture design. In all three designs,the least stress was when the implants were loaded in a lateral direction. The stress levels for cantilever andnon-cantilevered designs were nearly the samefor all the simulated designs. Conclusion: When tested under differentloading simulations, the three modelsshowed similar location and distribution ofstress patterns. Thus from the study it can beconcluded that the All-On-Four Concept is a clinically applicable treatment option for the atrophic edentulous ridges and induces least amount of stresseson the edentulous ridges. Therefore the overall longevity of the prosthesis is greatly enhanced.